2013
DOI: 10.1111/cen.12290
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term follow‐up study of eighteen patients with thyrotrophin‐secreting pituitary adenomas

Abstract: Our results demonstrate that patients with TSH-omas, who often present with large macroadenomas with extrasellar extension, have an excellent response to SSA therapy. Because the results of surgery and radiotherapy are disappointing, primary medical therapy may be considered in virtually all patients, except in case of optic chiasm compression, especially in those harbouring large adenomas with parasellar extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 37 publications
(95 reference statements)
1
17
2
1
Order By: Relevance
“…Although previous studies have shown the surgical outcome to be poor 7,9,23,34,35,38 (Table 5), we were able to achieve complete remission for 76 (84%) of the 90 patients in our study, including all 16 of the patients with microadenomas, 60 (81%) of the 74 with macroadenomas, and 8 (38%) of the 21 with cavernous sinus invasion. The different results may be partially explained by different criteria of remission and the small number of patients who received thyroid-targeted treatments among the studies.…”
Section: Surgical Treatmentcontrasting
confidence: 48%
See 3 more Smart Citations
“…Although previous studies have shown the surgical outcome to be poor 7,9,23,34,35,38 (Table 5), we were able to achieve complete remission for 76 (84%) of the 90 patients in our study, including all 16 of the patients with microadenomas, 60 (81%) of the 74 with macroadenomas, and 8 (38%) of the 21 with cavernous sinus invasion. The different results may be partially explained by different criteria of remission and the small number of patients who received thyroid-targeted treatments among the studies.…”
Section: Surgical Treatmentcontrasting
confidence: 48%
“…Given the high efficacy of somatostatin analogs (normalization of thyroid hormone levels in 95% and tumor shrinkage in 40% of the patients 4 ), van Varsseveld et al concluded that primary medical therapy may be considered in virtually all patients with TSH adenomas, except in those with optic chiasm compression. 35 However, when we take into account the fact that somatostatin analogs are expensive and treatment must be continued over a long period of time once started, surgery should be the first choice of treatment in patients with TSH-secreting adenomas as in patients with acromegaly or Cushing's disease if we can achieve surgical cure rates in the range of 60%-85%, which is almost similar to those of other types of functioning pituitary adenomas. Our current study can clearly demonstrate that a high surgical cure rate (84%) can be achieved by earlier proper diagnosis of TSH-secreting adenomas and aggressive tumor removal with adequate surgical approaches for various types of tumors.…”
Section: Preoperative Medical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] If surgery is contraindicated or if it fails to cure, the European Thyroid Association guidelines strongly recommend treatment with somatostatin analogs (SSA), such as octreotide and lanreotide, which have proved to be highly effective in a series of studies. [9][10][11][12][13][14][15][16][17][18][19] However, there are cases where manifestation of adverse effects, resistance to or escape from the inhibitory effect of SSAs lead to failure of treatment. 15,18,19 In these cases stereotactic irradiation can be employed.…”
Section: Introductionmentioning
confidence: 99%